The Impact of Research and Development (R&D) Expenditure on Productivity Growth: A Panel Data Evidence from the UK Manufacturing Sector - Onyekwere, Sixtus Cyprian (Asian Journal of Economics and Empirical Research, 2019)
This study focuses on the impact of Research and Development (R&D) expenditure on productivity growth for a panel of 13 UK manufacturing industries, using dataset from 1997 to 2014. The paper used the extended Cobb-Douglas production function, where R&D expenditure is included as one of the factor inputs, just like labour and capital. The study employs the fixed effects method for the panel data analysis and found R&D coefficient of 0.07, significant at 1%. The finding implies that, consistent with previous papers done for the UK manufacturing sector, R&D expenditure still has a positive relationship with productivity growth at panel industry level. However, the estimate 0.07 lends support to the argument of small coefficient for R&D, unlike other papers arguing for higher coefficient. Thus, we align with the argument that R&D has a small positive impact on productivity growth. Theoretical implication of this finding is that technological advancement which contributes to productivity growth is not exogenous; it can be determined by R&D decisions in firms and in industries. Thus, policy recommendation of this research is for the UK government to provide incentives to increase innovation in the UK manufacturing industries by increasing research grants and subsidies given to firms. Finaly, evidence from the result of this paper has shown that firms who wish to increase labour productivity should include R&D investment as one of their strategies.